Period poverty and mental health implications among college-aged women in the United States - Cardoso, Lauren F.; Scolese, Anna M.; Hamidaddin, Alzahra; Gupta, Jhumka (BMC women's health, 2021)
The purpose of this study is to examine the frequency of "period poverty," or not being able to afford sanitary products, among university students, and associations with poor mental health. An online survey was conducted with a nationally-drawn sample (N = 471) of college-attending women to assess the association between period poverty and depression. Period poverty was measured via two questions designed for this study; depression was measured with the standard PHQ-9. Multivariable logistic regression was utilized for analysis. Among our sample, 14.2% of women had experienced period poverty ever in the past-year; an additional 10% experienced it every month. Compared to those who had never experienced period poverty, adjusted analysis revealed that women with monthly past-year period poverty were the most likely to report moderate/severe depression (AOR = 2.34, 95% CI 1.09-4.99), followed by those who had experienced it ever in the past year (AOR = 1.83, 95% CI, 0.99-3.38). Many young women cannot afford menstrual health products to meet their monthly needs, and this may impact their mental well-being. Improved access to affordable menstrual products is needed to support these young women.